2014
DOI: 10.4293/jsls.2014.00166
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptance of a Robotic Surgery Ergonomic Training Program

Abstract: Background and Objectives:Assessment of ergonomic strain during robotic surgery indicates there is a need for intervention. However, limited data exist detailing the feasibility and acceptance of ergonomic training (ET) for robotic surgeons. This prospective, observational pilot study evaluates the implementation of an evidence-based ET module.Methods:A two-part survey was conducted. The first survey assessed robotic strain using the Nordic Musculoskeletal Questionnaire (NMQ). Participants were given the optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…The authors identified that only 16% of surgeons underwent any formal ergonomic training; however, when an educational program was implemented, 74% noted a decrease in strain when implementing the recommended positions. 20 Although the robotic surgical platform addresses and alleviates many of the ergonomic deficiencies associated with conventional laparoscopy, this modality has not fully alleviated the risk of MSK discomfort among surgeons. 64 During robotic procedures, the surgeon should always focus on a neutral position to avoid static loading on the body.…”
Section: Robotic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors identified that only 16% of surgeons underwent any formal ergonomic training; however, when an educational program was implemented, 74% noted a decrease in strain when implementing the recommended positions. 20 Although the robotic surgical platform addresses and alleviates many of the ergonomic deficiencies associated with conventional laparoscopy, this modality has not fully alleviated the risk of MSK discomfort among surgeons. 64 During robotic procedures, the surgeon should always focus on a neutral position to avoid static loading on the body.…”
Section: Robotic Surgerymentioning
confidence: 99%
“…The chair and console height can be readjusted at any time to provide a more comfortable position. 20,65 Due to the paucity of research comparing the ergonomics of robotassisted surgery versus conventional laparoscopy, further investigations are required to fully elucidate the surgeon's risk of work-related injury when using this technology. 66…”
Section: Robotic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…8 Studies in other surgical specialties suggest that injuries requiring surgical intervention and time away from work occur as early residency training, with one study stating that one trainee was required to prolong their training for 3 months due to occupational injury. [35][36][37][38][39] During an American College of Surgeons webinar, one attending stated that two of their trainees in recent years have required laminectomies and one of their colleagues was disabled from operating in their early 40s due to work-related MSDs. In addition to missed work, work-related MSDs and poor ergonomics have been shown to reduce productivity [40][41][42] leading to inferior operative performance.…”
Section: Discussionmentioning
confidence: 99%
“…Franasiak et al [95] used the NMQ to evaluate the MSD of surgeons during robotic surgery before and after an ergonomic improvement. The improvement programme was easily implemented and was well received.…”
Section: Other Fields Of Healthmentioning
confidence: 99%